Challenges and practices arising during public health emergencies: A qualitative survey on ethics committees. Issue 1 (12th February 2022) - Ekmekci, Perihan Elif; Güner, Müberra Devrim; Buruk, Banu; Güneş, Begüm; Arda, Berna; Görkey, Şefik
Abstract: The particular dynamics of public health emergencies urge scientists and Ethics Committee (EC) members to change and adapt their operating procedures to function effectively. Despite having previous pandemic experiences, ethics committees were unprepared to adapt to COVID‐19 pandemic challenges. This survey aims to learn and thoroughly discuss the most salient issues for ECs during the COVID‐19 pandemic. The results indicate that the main problems faced by ECs were lack of/insufficient regulations, lack of data/experience/knowledge, sloppy review, poor research design, and poor adaptation to quarantine measures. Coping with factors that threaten the autonomy and independence of ECs, the ethical dilemma regarding maximizing common good versus protecting the rights and well‐being of study participants, comprehending the change in the context of vulnerable populations, and redefining the role of ECs to strengthen trust in science and vaccine confidence were outstanding issues.